Pengembangan Bahan Ajar dengan Pendekatan Etnomatematika pada Materi Bangun Ruang Sisi Lengkung - Widayati Widayati; Mega Mardarisa (Lembaga Pengembangan Kinerja Dosen, 2025)
Many students have difficulty in learning mathematical concepts, especially in the material of curved-sided spatial figures, in addition, knowledge of regional culture is still lacking. This is due to the limited use of teaching materials in learning which has an impact on students' interest in learning. The purpose of this study is to develop teaching materials in the form of e-modules with an ethnomathematics approach to curved-sided spatial figures that are suitable for use, as an alternative to other teaching materials that can be used in learning. The type of research method used is the Research and Development (R&D) method with a 4D development model (Define, Design, Develop, Disseminate). The subjects of this study were grade IX students at SMPN 2 Kaledupa. The instruments used to measure the validity and practicality of the teaching materials developed were in the form of a validation questionnaire from material experts and media experts and a student response questionnaire. The data obtained from measuring validity and practicality were then processed using quantitative and qualitative descriptive analysis. The results of the research on the development of teaching materials with an ethnomathematics approach show that the developed learning e-module is declared feasible to use based on the assessment results of the material expert and media expert validators. The average score percentage obtained from the material expert validator is 89.06% with very valid criteria. While the average score percentage from the media expert validator is 86.45% with very valid criteria. In addition, the learning e-module with an ethnomathematics approach is also declared practical to use based on the results of the student response assessment. The average percentage of the overall student response assessment score is 89.93% with very practical criteria.